Health information and the choice of overall diet in urban China - Chen, Kevin Z.; Yu, Luyun; Lin, Wen; Ortega, David L. (Agricultural Economics Research Association, 2022)
Unhealthy diet is a leading factor for death and disability globally (WHO, 2021). Chinese diets have shifted substantially from the traditional plant-based diets to animal- and plant-based diets due to economic and social development (Huang et al., 2021). On average Chinese residents eat too much meat while having insufficient consumption of whole grains, fruits, nuts, and milk (Sheng et al., 2021). There exist significant gaps between the current Chinese diet and the healthy diets, such as the Chinese Food Guide Pagoda diet and the EAT-Lancet diet. As a result, China has the highest rate of diet-related cardiovascular disease deaths and cancer deaths and disability adjusted life-years worldwide (Afshin et al., 2019). This health burden would in turn reduce human capital and threaten life expectancy (Nishida, 2004; Willett and Stampfer, 2013). In response to these challenges, transforming the Chinese diet to healthy one is critical and urgent.